PENINGKATAN PENGETAHUAN PEMANTAUAN PERTUMBUHAN ANAK PADA KADER DAN GURU PAUD (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2024)
Indonesia bears a triple burden of malnutrition, namely undernutrition, overweight, and micronutrient deficiencies. The global economic crisis due to COVID-19 has produced lifestyle changes, including changes in dietary intake, that may increase malnutrition risks. The Indonesian Nutritional Status Survey 2022 data show an incidence of stunting of 15.2% in West Jakarta, well above the 2024 14% target determined by Indonesia’s President Joko Widodo in Presidential Regulation No. 72 for 2021 on accelerated stunting reduction. Various strategies have been formulated by West Jakarta’s municipal government, such as 3-month courses of nutritious food for children at risk of stunting. Available studies show that knowledge is associated with attitude and behavior.  At present, however, the effect of improving child growth monitoring knowledge through health promotion to cadres and early childhood education (PAUD) teachers in Kelurahan Jatipulo, West Jakarta, is still unknown. Therefore West Jakarta’s Administrative City Health Department invited the Faculty of Medicine of Universitas Trisakti to organize health promotion for family guidance team cadres and PAUD teachers as vanguards in child growth monitoring. Child growth standard usage questionnaires were distributed before and after health promotion, the results being that most respondents were ignorant or uncertain about growth chart usage, had never used growth chart in the previous year, and had never participated in growth chart usage training. Post-promotion knowledge level of cadres and teachers increased by 55% (p
Keywords: Family guidance cadres: teachers; knowledge; health promotion; stunting